Interim Report: Understanding wastewater treatment technologies for alternative water use: transformation of inorganic and organic nitrogen WP2: Monitoring and Data Collection Research Report No. CWQRC 2016-006 Curtin Water Quality Research Centre. - Linge, K.; Liew, D.; Gruchlik, Y.; Busetti, F.; Joll, Cynthia (2016)
In this report, we summarise collected data on the occurrence and removal of several anthropogenic chemicals in Western Australian Waste Water Treatment Plants (WWTPs) that differ in geographical location and design. Treatment efficiency was also characterised by monitoring nutrient concentrations. A wide variety of anthropogenic compounds were detected in the WWTPs. Wastewater treatments reduced the concentrations of some of these chemicals to varying extents, while other chemicals were persistent through treatment. While there was no consistent pattern in chemical removal at different WWTPs, preliminary results indicate that the simple pond systems generally performed less effectively compared to oxidation ditch and combined pond systems. Multivariate analysis of the DNA sequencing results indicated that microbiomes (i.e., the microbial DNA) associated with the treatment plants could be differentiated based on location, treatment stage and treatment technology. For 3 out of the 4 plants (WWTP 1, WWTP 3, WWTP 4), all influents were similar, but microbial communities after treatment varied widely, depending on the location or technology. The microbial community of WWTP 2 influent was different from the other treatment plants and the microbial profile remained similar even after treatment.